2012
DOI: 10.5815/ijcnis.2012.12.04
|View full text |Cite
|
Sign up to set email alerts
|

Performance of TCP Vegas, Bic and Reno Congestion Control Algorithms on Iridium Satellite Constellations

Abstract: Satellite networking is different from wired or wireless networks. The behavior and the performance of TCP/IP in normal wireless network as well as in wired network are different from one another. The TCP/IP protocol was not designed to perform well over high-latency or noisy channels so its performance over satellite networks are totally different. Each satellite networks/constellations have different properties. The deployment height, motion, direction, link capacityall differ from one satellite constellatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
2
6
0
Order By: Relevance
“…Of these studies, none examined two or more of the mechanisms included in this study. However, studies that examined latency found minimal differences between the latency achieved by different mechanisms [6], [8], [14], supporting the findings of this study.…”
Section: B Latencysupporting
confidence: 88%
See 3 more Smart Citations
“…Of these studies, none examined two or more of the mechanisms included in this study. However, studies that examined latency found minimal differences between the latency achieved by different mechanisms [6], [8], [14], supporting the findings of this study.…”
Section: B Latencysupporting
confidence: 88%
“…Research into TCP congestion control mechanisms aims to improve the performance of existing congestion control mechanisms, usually measured based on throughput [7], [14], goodput [15], [8], or link utilisation [16]. As different throughput metrics have been utilised across these studies, direct comparisons between the results of studies utilising throughput, goodput and link utilisation are infeasible, the performance of congestion control mechanisms is examined, relative to others evaluated by the same study.…”
Section: A Performance Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous research made on Iridium satellite constellations (Nirmala and Pujeri, 2012)0 has proved the results of Vegas to be good and the comparative analysis among two satellite constellations Teledesic and Iridium will explore better data transmission over satellite networks.…”
Section: Discussionmentioning
confidence: 99%